Analogue aerial-photopraphs external orientation reconstruction based on geoportal data - Dzieszko, Piotr (Quaestiones Geographicae, 2011)
For acquisition of source data for geoinformation analyses is necessary to do some field works. This way of data acquisition is time-consuming. In this case, photogrammetric and remote sensed methods can be more effective choice. Especially orthophotomap extracting is more effective process in creation of geodata. It is good foundation for further analysis and nice extension of existing geographical information systems. Despite fast growth of photogrammetry there are plenty of analogue, archival airphotos which can be used for geoinformation analysis. They are quiet up to date and scanned in very high resolution which means they can be used for really reliable analysis. The problem is very important because many of analogue, archival air photos do not contain photogrammetric warp. The aim of this paper is expression of applicability of geoportal webpage, which is part of INSPIRE directive, that can be used for external orientation reconstruction when there is no other georeference data.